Internationalization and the performance of born-global SMEs: the mediating role of social networks - Zhou, Lianxi; Wu, Wei-ping; Luo, Xueming (Journal of International Business Studies, 2007)
This paper offers a social network explanation for the purported relationship between internationalization and firm performance in the context of born-global small and medium enterprises (SMEs). We argue that home-based social networks play a mediating role in the relationship between inward and outward internationalization and firm performance. The mediating mechanism is attributed to three information benefits of social networks: (1) knowledge of foreign market opportunities; (2) advice and experiential learning; and (3) referral trust and solidarity. Using survey data from SMEs in the largest emerging economy of China, we found some support for this mediating role of social networks in the form of guanxi. The results imply that international business managers should consider social networks as an efficient means of helping internationally oriented SMEs to go international more rapidly and profitably.